Constructed Languages and Translation: Comparing Conlang Translation with Natural Language Translation - Hietaranta, Pertti (RiCOGNIZIONI. Rivista di Lingue e Letterature straniere e Culture moderne, 2022)
The main question paper discusses is the question as to how we can make sure that a translation into a conlang is acceptable (adequate, correct) despite the fact that there are by definition no native speakers of conlangs. The question is of relevance to practical translation work as well as translation studies even more generally since there are also natural languages for which there are no native speakers to consult on matters of translation correctness or acceptability. A major theme inside this main topic is the question as to who qualifies and on what grounds as an expert who can pass judgements on translation quality in general.